2022
DOI: 10.1111/prd.12427
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis, chronic liver diseases, and the emerging oral‐gut‐liver axis

Abstract: Periodontitis is an oral chronic inflammatory disease which has been associated with a wide range of systemic disorders some of which include diabetes, inflammatory bowel diseases, cardiovascular diseases, cancer, neurodegeneration, rheumatoid arthritis, and chronic liver diseases. [1][2][3][4][5][6][7] Periodontitis and these systemic conditions all share some degree of similarity in their pathophysiology which is characterized by a long-lasting deregulated inflammatory response.Today it is recognized that ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 169 publications
(446 reference statements)
1
57
0
Order By: Relevance
“…These ectopically colonized oral pathogens may also disseminate to the liver where they can exacerbate liver disease. Albuquerque‐Souza and Sahingur 48 review this oral–gut–liver microbial and immune axis and its medical implications. If this axis is adequately understood, it could lead to novel insights into the pathogenesis of periodontitis and comorbid diseases, such as chronic liver disease including non‐alcoholic fatty liver disease (NAFLD), which is a major focus of these authors’ review.…”
Section: Chronic Liver Diseasementioning
confidence: 99%
“…These ectopically colonized oral pathogens may also disseminate to the liver where they can exacerbate liver disease. Albuquerque‐Souza and Sahingur 48 review this oral–gut–liver microbial and immune axis and its medical implications. If this axis is adequately understood, it could lead to novel insights into the pathogenesis of periodontitis and comorbid diseases, such as chronic liver disease including non‐alcoholic fatty liver disease (NAFLD), which is a major focus of these authors’ review.…”
Section: Chronic Liver Diseasementioning
confidence: 99%
“…periodontal disease or dental caries) or systemic diseases (e.g. diabetes, cancer, endocarditis, systemic infections), where the unbalanced microbiome may be the trigger for the pathology, has been demonstrated (Albuquerque-Souza and Sahingur 2022 ; Al-Qadami et al 2022 ; Khor et al 2021 ). The interplay between the external factors and the colonization or proliferation in the oral cavity of some bacterial groups may be the key to prevent and control some pathologies.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Considering that a milliliter of saliva may contain 8–9 log-units of microbial cells, some of which can multiply every 3–4 h, it can be estimated that 1–3 g of microbial biomass can be ingested per day (Edgar et al 2012 ). Given the capacity of some of these microbial cells to survive and colonize the host’s gut, a balanced and stable oral microbiota is an essential barrier to prevent pathogen colonization and infection and, therefore, oral and/or systemic infections and/or inflammatory symptoms (Albuquerque-Souza and Sahingur 2022 ; Ren et al 2021; Sampaio-Maia et al 2016 ; Willis et al 2020 ). The interface environment-human has received a renewed attention under the One Health perspective that considers a continuum between humans, animals, and the natural environment (Cunningham et al 2017 ; Osterhaus et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gut-brain communication is due to the bacterial-trigeminal nerve interaction. Therefore, the oral-brain and gut-brain axis are in a bi-directional relationship [ 67 , 68 , 69 , 70 ]. It was reported that frequent oral hygiene care has a negative connection, and infrequent oral hygiene behavior has a positive connection with the risk of stroke incidence [ 71 ].…”
Section: Orodental Healthmentioning
confidence: 99%